PERTUMBUHAN DAN HASIL KEDELAI DENGAN PENGGUNAAN AMELIORAN BATU KARANG PADA LAHAN RAWA LEBAK MENGGUNAKAN TEKNOLOGI BUDIDAYA JENUH AIR - Edi Susilo; Andreani Kinata; Dian Novita (University of Prof. Dr. Hazairin, SH, 2019)
Soybean is one of the secondary crops that has a good economic value. Soybean needs are increasing with increasing population, but production is not sufficient. Extensification programs can be carried out in sub-optimal swamp swamps with water saturated cultivation technology. Low pH and high Al and Fe are the main obstacles. One of the strategies taken is the provision of coral ameliorants. The aim of this study was to obtain information on the effectiveness of coral reefs to improve the cultivation of black soybean in swamp swamps. The study was conducted in March - May 2018 at the Experimental Garden of the Faculty of Agriculture, University of Ratu Samban Arga Makmur Bengkulu Utara. The study used a randomized block design with factorial patterns. The first factor in the dose of ameliorant per plant consisted of: P0: control, P1= 5 g, P2 = 6 g, P3= 7 g, P4= 8 g, P5= 9 g, P6= 10 g. The second factor when the ameliorant application consists of: W1= 4 weeks before planting (MBT), W2 = 3 MBT, W3 = 2 MBT, W4 = 1 MBT, W5= when planting, W6= 1 weeks after panting. The results showed that the treatment of the dose and time of application of coral ameliorants had a very significant effect on plant height and number of leaves. There is no real interaction between the dose and time of ameliorant application to all variables. The best dose of ameliorant treatment is 9 g per plant and can increase the height and number of leaves per plant. When the application of 1 MBT and 1 MST is able to produce the best height and number of leaves.